1982
DOI: 10.1002/cne.902060304
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural identification of labeled neurons in the dorsal motor nucleus of the vagus nerve following injections of horseradish peroxidase into the vagus nerve and brainstem

Abstract: The efferent connections of two types neurons in the dorsal motor nucleus of the vagus nerve (DMV) were studied in the cat by light and electron microscopy following horseradish peroxidase (HRP) injections into the cervical vagus nerve or brainstem. After injections of HRP into the vagus nerve, up to 80% of medium-sized neurons averaging 26 x 20 micrometers in 1-micrometer-thick sections were retrogradely labeled while no small neurons were labeled in the DMV. Incubation with either diaminobenzidene (DAB) or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 27 publications
(1 reference statement)
3
14
0
Order By: Relevance
“…Morphologically, they resemble neurones described by Cajal (1909) as dorsal vagal motor neurones and shown using immunohistochemical techniques to be cholinergic (Armstrong, Clifford, Levey, Wainer & Terry, 1983) or monoaminergic (Ritchie, Westlund, Bowker, Coulter, & Leonard, 1982). Their axon trajectory follows the same course as that described by retrograde HRP labelling of the vagus nerve in rats (Kalia & Sullivan, 1982;McLean & Hopkins, 1982).…”
Section: Organization Of the Solitary Complex Discussionsupporting
confidence: 68%
“…Morphologically, they resemble neurones described by Cajal (1909) as dorsal vagal motor neurones and shown using immunohistochemical techniques to be cholinergic (Armstrong, Clifford, Levey, Wainer & Terry, 1983) or monoaminergic (Ritchie, Westlund, Bowker, Coulter, & Leonard, 1982). Their axon trajectory follows the same course as that described by retrograde HRP labelling of the vagus nerve in rats (Kalia & Sullivan, 1982;McLean & Hopkins, 1982).…”
Section: Organization Of the Solitary Complex Discussionsupporting
confidence: 68%
“…We found that there were small neurons in the AmC that do not project to the alimentary t,ract. Their morphology is similar to that of the small interneurons in the dorsal motor nucleus of the vagus nerve (McLean and Hopkins, 1982). Afferent inputs of the swallowing reflex originating from the surface of the tongue, the soft palate, and the pharynx Cell size (area pm2) USDE n. MCE n. B P H n. enter the nucleus of the solitary tract and the sensory trigeminal nucleus (Miller, 1982;Altschuler et al, 1989).…”
Section: Discussionmentioning
confidence: 97%
“…It seems certain that these neurones do not project down the vagus to the crush or labeling site at the mid-cervical level. They are either local interneurones or project to other brain areas; McLean and Hopkins (1982) were able to establish projections to other parts of the brain for about 10% of these smaller neurones in the cat.…”
Section: Discussionmentioning
confidence: 99%